(untitled) (International Seven Journal of Multidisciplinary, 2023)
Case presentation: MIBV patient, female, 75 years old, diagnosed with diverticular disease of the colon for years, with sporadic episodes of diverticulitis, however in 2019 the pictures of acute diverticulitis began to increase in frequency. With several episodes of diverticulitis and conservative treatments, 2019 had 4 episodes, presenting sigmoid colon thickening suggestive of neoplasia, but discarded with colonoscopy, in 2020 patient presented 5 episodes and in 2021 6 episodes in a period of 6 months, generating a picture of chronic pain and altered bowel habit. Surgery was indicated, and an elective open rectosigmoidectomy was performed; the patient received a diet on the second postoperative day and was discharged on the fifth day. Maintained outpatient follow-up with no new episodes. Discussion: Most patients with acute sigmoid diverticulitis are treated clinically, surgery is only indicated when the diverticulitis is untreatable or refractory to clinical therapy, about 10% to 15% of patients require surgery. For patients who require surgery for diverticulitis, the choice of technique depends on the patient’s hemodynamic stability, extent of peritoneal contamination, and surgeon experience/preference. The major benefit of surgical treatment of diverticular disease is the cessation of episodes of diverticulitis, as studies show that patients with 1 or 2 episodes of acute diverticulitis, treated medically, required surgery for recurrent disease in up to 45% of cases. Final Comments: Indications for surgical treatment should be individualized to achieve the best outcome, as shown in this case, in which elective surgery resulted in complete cessation of diverticulitis episodes. The choice of resection method, open or laparoscopic, should consider the availability of equipment and the physician’s training for the procedure, always taking into account the best resolution with fewer complications and mortality. Abbreviations and acronyms: IQR: interquartile range, CT: computed tomography, USG: ultrasonography DOI: 10.56238/isevmjv1n2-004